2016
DOI: 10.1016/j.protis.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba and Dictyostelium Use Different Foraging Strategies

Abstract: Amoeba often use cell movement as a mechanism to find food, such as bacteria, in their environment. The chemotactic movement of the soil amoeba Dictyostelium to folate or other pterin compounds released by bacteria is a well-documented foraging mechanism. Acanthamoeba can also feed on bacteria but relatively little is known about the mechanism(s) by which this amoeba locates bacteria. Acanthamoeba movement in the presence of folate or bacteria was analyzed in above agar assays and compared to that observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Overall, this study demonstrates that amoeba will move in a similar forward direction despite having readily available nutrients at their current location, even if the movement is slightly slower and is nutrient type dependent. These differences between strains allude to strain-dependent proclivities of what makes migration more or less important to an amoeba, which is similar to previous studies indicating that Acanthamoeba move robustly in all directions regardless of density or presence of folate [ 19 ]. While the natural assumption may be that both strains would be chiefly interested in conservation of energy, ATCC 50370 maintained its movement regardless of surface or nutrient availability.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, this study demonstrates that amoeba will move in a similar forward direction despite having readily available nutrients at their current location, even if the movement is slightly slower and is nutrient type dependent. These differences between strains allude to strain-dependent proclivities of what makes migration more or less important to an amoeba, which is similar to previous studies indicating that Acanthamoeba move robustly in all directions regardless of density or presence of folate [ 19 ]. While the natural assumption may be that both strains would be chiefly interested in conservation of energy, ATCC 50370 maintained its movement regardless of surface or nutrient availability.…”
Section: Discussionsupporting
confidence: 84%
“…Reduced plaque growth rates can potentially result from defects in the ability of cells to properly forage for bacteria at the perimeter of the plaque. Dictyostelium forage for bacteria primarily using the folate receptor and downstream G proteins as a mechanism to facilitate chemotactic movement [42, 43]. The erk2 − cells displayed a defect in folate chemotaxis similar to that of far1 − and gα4 − mutants when analyzed in an above agar assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is known that Acanthamoeba can feed on bacteria, little is known about the mechanisms through which the amoebae locate the bacteria. Comparing it with an amoeba that uses chemotaxis, Dictyostelium , it was revealed that Acanthamoeba do not use chemotaxis as the primary mechanism to find bacterial food sources (Kuburich et al 2016 ). Interestingly, in an experiment comparing the ability of ciliates and Acanthamoeba , it was revealed that the competition was asymmetric in favour of the ciliates, but Acanthamoeba had better long‐term negative effect, both in the open‐water phase as well as in biofilm, on bacterial biomass (Zhang et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%